Fungi that are medically relevant to humans and their prospect in a global warming scenario - Bernardo Franco; Naurú Idalia Vargas-Maya; Felipe Padilla-Vaca; Fátima Berenice Ramírez-Montiel; José Ascención Martínez-Álvarez (Academia Molecular Biology and Genomics)
Pathogenic fungi are medically important organisms that have recently attracted a great deal of attention due to their exacerbated virulence in an uncontrolled global warming scenario. The identification, treatment, and control of these fungi are time consuming and complicated. This review focuses on the most important aspects of some of these fungi, specifically from the genera Sporothrix, Cryptococcus, Histoplasma, and Paracoccidioides. It also explains how the biological traits of these fungi allow them to adapt to their surrounding environment and evade the host immune system. Their ability to survive in different cellular forms makes the treatment and control of infections and outcomes more complicated. Finally, we discuss and provide data suggesting the prevalence of pathogenic fungi is a major threat to human health in developing countries due to increasing global warming.